You are on page 1of 9

1

1)( z n ) ' = nz n 1 , (n)

1
1
2 ' = 2
z
z

( z + z ) n z n
= lim (nz n 1 + Cn2 z n 2 z + " z n 1 ) = nz n 1
z 0
z 0
z
1
1

1
1
1
2 ' = lim z + z z = lim
= 2
z 0 z ( z + z )
z
z
z z 0

1 ( z ) ' = lim
n

2
1 f (z ) = x 2 i y
3

2 f ( z ) = 2 x + 3 y i
3

f (z) = xy2 + i x2 y

4 f ( z ) = sin xchy + i cos xshy

u
v
v
u
= 0,
= 0,
= 1
= 2 x,
y
x
y
x

1
z x = u,v C-R f (z ) = u + i v = x i y
2
1
x = z
2

u
u
v
v
= 6x2
= 0 = 0 = 9 y2
x
x
y
y

z 2 x = 3 y , 2 x 3 y = 0 u,v C-R
2

f ( z ) = u + i v = 2 x 3 + 3 y 3i 2 x 3 y = 0 z
3

u
v
v
u
= 2 xy
= x2
= 2 xy
= y2
y
y
x
x

z z=0 u,v C-R f (z ) = xy 2 + i x 2 y z = 0


z
4

u
u
v
v
= cos xchy
= sin xshy = sin xshy = cos xchy
x
y
x
y

z u,v C-R f ( z ) = sin xchy + i cos xshy


z z
3 f ( z )
1 ( z 1)

2 z + 2iz

az + b
(c, d0)
cz + d

z 1

4
1 f ( z ) = 5( z 1) f (z ) z

2 f (z ) = 3 z 2 + 2 i f (z ) z
3 f (z ) =

(z

2 z
2

2z
(z 1)2 (z + 1)2

f (z ) z = 1 z z = 1 f (z )
1

4 f ( z ) =

ad bc
f (z ) z = d / c(c 0)
(cz + d ) 2

f ( z ) D

f ( z ) D

f ( z ) z0

f ( z ) z0

f ( z ) z0
1 z0
z0 D D
22
6
1 f (z ) z 0 f (z0 )
2 f (z0 ) f (z ) z 0
3 z 0 f (z ) f (z ) z 0
4 z 0 f (z ) g ( z ) z 0 f ( z ) + g ( z ) f ( z ) / g ( z )
5 u ( x, y ) v( x, y ) f ( z ) = u + iv
6 f ( z ) = u + iv u f ( z ) D
v f ( z ) D

1 f (z ) =| z | 2 = x 2 + y 2 z z=0
2 f (z ) =| z | 2 z=0 z=0
3 f ( z )z0z0 f ( z )
4 f ( z ) = sin x ch y, g ( z ) = i cos x sh y z = ( / 2, 0)
f ( z ) + g ( z )
5 f (z ) = z Re z = x 2 + i xy z=0 C-R f ( z ) z=0

6 u C-R v f ( z ) D

7 f (z ) = u + i v z
2



2
| f (z ) | + | f (z ) | =| f ' (z ) |
x
y

| f (z ) |= u 2 + v 2


| f (z ) |=
x

u
v
v
u
u
+v
+v

y
x
x
| f (z ) |=
2
2
2
2
y
u +v
u +v

f (z ) = u + i v
u v
u
v
=
=

x y
y
x

2
2
2
2

1 2 u
v


2
| f (z ) | + | f (z ) | = 2 2 u + u
u + v x
x
y
x

2
2
u v
v u
v
u
+ 2uv
+ v 2 + v 2 + 2uv
x x
x x
x
x

2
2
u 2 v 2

v
2
2 u
+
+
+
u
v

x x
x x

1
u 2 + v2

1
u 2 + v 2 | f (z ) |2 =| f (z ) |2
u + v2

9-
u 1 v
v
1 u
=
=
r
r
r r

x = r cos , y = r sin u, v C-R


u u
u
=
cos + sin
r x
y
v v
v
u
u
u
= ( r sin ) + r cos =
r sin +
r cos = r
x
y
y
x
r

u 1 v
=

r r
u u
=
( r sin ) + u r cos
x
y
v v
v
u
u
= cos + sin = cos + sin
r x
y
y
x

1 u
1 u
u
= r cos r sin =
r y
r
x

u 1 v
v
1 u
=
=

r r
r
r

10 f (z ) = u + iv D f (z )
1 f (z )
2 f (z ) D
3 | f (z ) | D
4 arg f (z ) D
5 au + bv = c a b c
3

1 f (z ) v = 0 f (z ) D C-R
u
v
u v
=
=
= 0
=0
x y
y
x

u D u = C ( ) f ( z ) = u + iv = C
2 f (z ) = u + iv = u iv D
u ( v )
v

=
=
x
y
y

u
( v ) u
=
=
y
x
x

f ( z ) = u + iv D
u
v
u v
=
=

x y
y
x

1
2
u u v v
=
=
=
= 0
x y x vy

u, v D
u1 = C1 , u 2 = C 2 (C1 , C 2 )

f (z ) = u + iv = C1 + iC 2 = C

3 | f (z ) | D C1 u 2 + v 2 = C12 x y
v
u
2u x + 2v x = 0
u
v
2u
+ 2v
=0
y
y

f (z ) D C-R

u v u
v
=
,
=

x
x y y

u
u
u x v y = 0
u
u
v
+u
=0
x
y

v v
u v
=
= 0
=
= 0 u, v u = C1 , v = C 2
x y
x vy

f (z ) = u + iv = C1 + iC2 = C

4 arg z D C1 f (z ) 0 f (z ) = u + iv 0
v

u>0
arctan u ,

v
arg f (z ) = arctan + , u < 0, v > 0
u

arctan v , u < 0, v < 0

u
C1

= C1 +
C
1

u >1
u < 0, v > 0
u < 0, v < 0

arg f (z ) x y
4

u
1 v
v u v v u
u
2
x
u x
x = 0
= x2
2
2
u
v
+
v
1+
u
1
u2

v
u
v
u
u
v u
v
y
y
y
y
=
=0
2
2
2
u +v
v
1+
u

f (z ) C-R
u
u
v x u y = 0
u
u
u
v
=0
y
x

u u
u v
=
= 0
=
= 0 u v C 2 C 3
x y
x y

f (z ) = u + iv = C 2 + iC 3 = C

5 au + bv = c a b c a b 0 a 2 + b 2 0
a b c au + bv = c x y
v
u
a x + b x = 0
u
v
a
+b
=0
y
y

f (z ) = u + iv u v C-R
u
u
a x b y = 0
u
u
b
+a
=0
y
x

u u
v v
=
= 0
=
= 0 f (z )
x y
x y

11.
1 e z = e z

2 cos z = cos z

3 sin z = sin z

1 e z = e x (cos y + i sin y ) = e x (cos y i sin y ) = e x i y = e z

ei z + e i z 1 i z
= e + e i z = 1 (e i z + ei z ) = cos z
2 cos z =

2
2
2

3 sin z =
=

1 iz
1 iz
1
e e i z =
e e i z =
( e i z e i z )
2i
2i
2i
1 iz
e e i z = sin z
2i

12
3 1 + e = 0

4 sin z + cos z = 0

3 e = 1
z

z = Ln( 1) = ln | 1 | + i[arg( 1) + 2k ] = i (1 + 2k )

k = 0,1,2,"

ei z e i z
1
= ( ei z + e i z )
2i
2

4 sin z = cos z ,

e2i z 1 = i e2i z + 1
e2i z =

z=

1 i
1+ i

1
1
1 i 1
Ln
= Ln( i ) = [ln | i | + i(arg( i ) + 2k )]
2i 1+ i 2i
2i
=

i
1

+ 2k = k , k = 0,1,2, "
2i 2
4

13
1 cos(z1 + z2 ) = cos z1 cos z2 sin z1 sin z2 ;
sin (z1 + z2 ) = sin z1 cos z2 cos z1 sin z2 ;

2 sin 2 z + cos 2 z = 1 3 sin 2 z = 2 sin z cos z 4 tan 2 z =

2 tan z

1 tan 2 z

5 sin z = cos z cos(z + ) = cos z


2

6 | cos z | = cos x + sh y,| sin z | = sin x + sh y


2

1 = cos(z1 + z2 ) =

1 i ( z1 + z 2 ) i ( z1 + z 2 )
e
+e
2

= cos z1 cos z2 sin z1 sin z2


=

e i z1 + e i z1 e i z2 + e i z2 e i z1 e i z1 e i z2 e i z2

2
2
2i
2i

e i ( z1+ z2 ) + e i ( z1 z2 ) + e i ( z1 z2 ) + e i ( z1 + z2 ) + e i ( z1 + z2 ) e i ( z1 z2 ) e i ( z1 z2 ) + e i ( z1+ z2 )
4

e i ( z1 + z2 ) + e i ( z1+ z2 )
2

= cos( z1 + z 2 ) = cos z1 cos z 2 sin z1 sin z2


= sin (z1 + z 2 ) =

1 i ( z1+ z2 ) i ( z1 + z2 )
e
e
2i

= sin z1 cos z 2 + cos z1 sin z 2

) (

) (

) (

1 i z1
1 i z2
1
1 i z2
e e i z1
e e i z2 + e i z1 + e i z1
e e i z 2
2i
2
2
2i

1 i ( z1 + z 2 ) i ( z1 z 2 ) i ( z1 z 2 ) i ( z1 + z 2 )
1 i ( z1 + z2 ) i ( z1 z2 ) i ( z1 z2 ) i ( z1 + z2 )
e
+e
e
e
+
e
e
+e
e
4i
4i

1
1 i ( z1 + z2 ) i ( z1 + z2 )
2ei ( z1+ z2 ) 2e i ( z1 + z2 ) =
e
e
4i
2i

= sin (z1 + z2 ) = sin z1 cos z2 + cos z1 sin z2


2

ei z e i z ei z + e i z
+

2 sin 2 z + cos 2 z =
2i
2i

1 i2z
e e i 2 z
2i

3= sin 2 z =

= 2 sin z cos z = 2
=

) (

1 2i z
1
e 2 + e 2 i z + e 2 i z + 2 + e 2 i z = 1
4
4

) (

1 iz
1 iz
e e i z
e + e i z
2i
2

1 i2z
1 i2z
e + 1 1 e i 2 z =
e e i 2 z
2i
2i

sin 2 z = 2 cos z sin z

sin 2 z
2 sin z cos z
sin z
4 tan 2 z =
=
=2
cos 2 z cos 2 z sin 2 z
cos z

sin z 2
2 tan z
1
=
2
cos
z
1 tan z

51

sin z = sin + ( z ) = sin cos( z ) + cos sin ( z )


2
2
2

2
= cos( z ) =

1 i ( z ) i ( z ) 1 iz iz
e
+e
= e +e
2
2

= cos z
cos(z + ) = cos z cos sin z sin = cos z

6 | cos z | =| cos x ch y i sin x sh y | = cos x ch y + sin x sh y


2

cos x (1 + sh y ) + sin x sh y = cos x + sh y


2

| sin z | =| sin x ch y + i cos x sh y | = sin x ch y + cos x sh y


2

sin x(1 + sh y ) + cos x sh y = sin x + sh y


2

141 y | sin( x + iy ) | | cos( x + iy ) |


2 t | sin t | 1 | cos t | 1

1 | sin z |=|

eiz e-iz | e y e y |
|
| cos z |
2i
2

| e y e y |
y
2 t = iy, y R | sin t |=
2
15 Ln( i ) Ln( 3 + 4 i )

Ln( i ) = Ln | i | + i(arg( i ) + 2k ) = i + 2k
2

= i 2k , k = 0,1,2, "
2

ln ( i ) = ln | i | + i arg( i ) =

i
2

Ln( 3 + 4 i ) = ln | 3 + 4 i | + i[arg( 3 + 4 i ) + 2k ]

4
= ln 5 + i arctan + 2k
3

= ln 5 i arctan (2k + 1) , k = 0,1,2, "


3

ln ( 3 + 4 i ) = ln | 3 + 4 i | + i arg( 3 + 4 i ) = ln 5 + i arctan
3

161 Ln( z1 z2 ) = Ln z1 + Ln z2 2 Ln( z1 / z2 ) = Ln z1 Ln z2


1 Ln( z1 z2 ) = ln(| z1 z2 |) + i Arg z1 z2 = ln z1 + ln z2 + i Arg z1 +i Arg z2 = Ln z1 + Ln z2
2 Ln( z1 / z2 ) = ln(| z1 / z2 |) + i Arg z1 / z2 = ln z1 ln z2 + i Arg z1 -i Arg z2 = Ln z1 Ln z2
171 Ln z = 2 Ln z 2 Ln
2

z=

1
Ln z
2

1 Ln z = 2 ln | z | +i Arg(2 z ), 2 Ln z2 ln | z | +2i Arg( z )


2

1
1
1
i
z = ln | z | +i Arg( z ), Ln z ln | z | + Arg( z )
2
2
2
2

2 Ln

18 e

1 i

1i
4

exp

i
i
3 (1+ i )

1i

= ee

1i
exp
4

i ln 3+ i ( arg3+ 2 k )

= e cos i sin = i e
2
2

1
1
i

2 14

4 4
4
e (1i )
= e e = e cos i sin =
4
4 2

3i = ei Ln 3 = e

(1 + i )

= e 2 k ei ln 3 = e 2 k (cos ln 3 + i sin ln 3),

k = 0,1,2, "

i ln|1+ i|]+ i ( arg (1+ i ) + 2 k )

= ei Ln (1+i ) = e [

=e

ln 2

+ 2 k
2 4

=e

19 ( z ) ' = az
a

a 1

+ 2 k
4

ln 2
ln 2

+ i sin
cos

2
2

k = 0,1,2, "

1
( z a ) ' = (e a ln z + 2 k i ) ' = a(ln z ) ' e a ln z + 2 k i = a z a = az a 1
z

20 1 ch z sh z = 1 2 sh z + ch z = ch 2 z
2

3 sh ( z1 + z2 ) = sh z1 ch z2 + ch z1 sh z2 ch ( z1 + z2 ) = ch z1 ch z2 + sh z1 sh z2
1 ch z sh z = (
2

2 sh z + ch z = (
2

e z + e z 2 e z e z 2
) (
) = 1
2
2

e z e z 2 e z + e z 2 e2 z + e2 z
= 1
) +(
) =
2
2
2

(e z1 e z1 )(e z2 + e z2 ) (e z1 + e z1 )(e z2 e z2 ) e z1 + z2 e z1 z2
+
=
3 sh z1 ch z2 + ch z1 sh z2 =
4
4
2
= sh ( z1 + z2 )
8

211 sh z = 0 2 ch z = 0 3 sh z = i

1 sh z = 0 e

2 ch z = 0 e

2z

2z

=1 z =

1
Ln1 = i k , k = 0, 1, 2,"
2

1
(2k + 1)
Ln(1) =
i , k = 0, 1, 2,"
2
2

= 1 z =

1
2

3 sh z = i e = i z = Ln i = i(2k + ) , k = 0, 1, 2,"
z

23: sh z Arsh z = Ln( z +

sh w = z

z 2 + 1)

e w e w
= z e 2 w 2 ze w 1 = 0 e w = z + z 2 + 1 ,
2

w = Arsh z = Ln( z +

z 2 + 1)

24 f ( z )
1 (z + i )2

2 z

z2 +1

1 V (z ) = f ' (z ) = 2(z + i ) = 2(z i )


f (z ) = (z + i ) = [x + i( y + 1)] = x 2 ( y + 1) + i 2 x( y + 1)
2

x( y + 1) = C1 x 2 ( y + 1)2 = C 2
2 V (z ) = f ' (z ) = 3z 2 = 3z 2 f (z ) = z 3 = x(x 2 3 y 2 ) + i y (3 x 2 y 2 ) ,
(3x 2 y 2 )y = C1
3
f (z ) =

x (x 2 3 y 2 ) = C2

2z
1 2z
V (z ) = f ' (z ) = 2
' = 2
' = 2
2
z + 1 z + 1
z +1

1
1
x 2 y 2 + 1 i 2 xy

= 2
= 2
2
z + 1 x y + 1 + i 2 xy
x y 2 + 1 + 4x2 y 2

(x

xy
2

y + 1 + 4x2 y2
2

=C1

x2 y2 + 1
= C2
x2 y2 + 1 + 4x2 y2